2017
DOI: 10.3390/w9040241
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Drought Hazard Assessment under Climate Change Scenarios in Semi-Arid Regions—A Case Study of the Karkheh River Basin in Iran

Abstract: Studies using Drought Hazard Indices (DHIs) have been performed at various scales, but few studies associated DHIs of different drought types with climate change scenarios. To highlight the regional differences in droughts at meteorological, hydrological, and agricultural levels, we utilized historic and future DHIs derived from the Standardized Precipitation Index (SPI), Standardized Runoff Index (SRI), and Standardized Soil Water Index (SSWI), respectively. To calculate SPI, SRI, and SSWI, we used a calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 61 publications
(38 reference statements)
6
37
0
Order By: Relevance
“…As shown, more than 50% of the observed discharges are within the 95PPU bands depicted with green shades in all configurations, except C3L1 and C3L2, where significant overestimations can be noticed, especially after 2000. A significant decrease is recorded in the observed values in the region at the end of the period due to severe droughts occurring after 2000 [44]. This can also be noticed in the temporal variation of rainfall for these datasets ( Figure S2).…”
Section: Model Performance and Parameterssupporting
confidence: 53%
“…As shown, more than 50% of the observed discharges are within the 95PPU bands depicted with green shades in all configurations, except C3L1 and C3L2, where significant overestimations can be noticed, especially after 2000. A significant decrease is recorded in the observed values in the region at the end of the period due to severe droughts occurring after 2000 [44]. This can also be noticed in the temporal variation of rainfall for these datasets ( Figure S2).…”
Section: Model Performance and Parameterssupporting
confidence: 53%
“…In this special issue, Kamali et al [8] address the issue of the existence of many datasets and their effects on the assessment of water resources. They combined 4 different climate data with 2 different land-use maps to build 8 different models that they calibrated and validated.…”
Section: Inadequate Definition Of the Base Modelmentioning
confidence: 99%
“…11-Kamali et al [8] studied the impact of different databases on the water-resources estimates and concluded that while different databases may produce similar calibration results, the calibrated parameters are significantly different for different databases. They highlighted that "As the use of any one database among several produces questionable outputs, it is prudent for modelers to pay more attention to the selection of input data".…”
Section: Appendix Amentioning
confidence: 99%
“…Moreover, von Gunten et al () used drought indices and the HydroGeoSphere hydrological model to project hydrological impacts of droughts in the context of climate change in the Lerma catchment (Spain) and indicated an increase in drought severity in the future. In another study, Kamali et al () assessed meteorological, agricultural and hydrological droughts in the Karkheh River Basin (Iran) using three drought indices and Soil and Water Assessment Tool (SWAT) and found that the frequency of extreme droughts is predicted to increase in the future. In those studies, a common implemented approach is using a hydrological model with two input data sets; one is historical hydro‐meteorological data from observations, and another is projected data through outputs of the general circulation models (GCMs) and the hydrological model.…”
Section: Introductionmentioning
confidence: 99%
“…The three drought indices have been widely used to evaluate the agricultural and hydro‐meteorological droughts (e.g. Leng et al , ; Kamali et al , ). Regarding the hydrological modelling, the SWAT model has been popularly used as a modelling tool to study on climate change impact on hydrology at a catchment scale.…”
Section: Introductionmentioning
confidence: 99%